KAIDAH FIQHIYYAH KE-5: ADAT SEBAGAI DASAR PENERAPAN HUKUM ISLAM - Muhammad Rasyid; Muhammad Syahidan; Fauzan; Raudatul Jannah (Institut Agama Islam Darul Ulum Kandangan, 2025)
This article examines the fifth fiqh maxim, al-‘adah muhakkamah (custom is authoritative), focusing on its operationalization as a legitimate basis for the application and determination of Islamic law. Through a socio-legal case study of the Kenyah indigenous community in Pampang Village, Samarinda, East Kalimantan, this research demonstrates how local adat, particularly in marriage and divorce functions not only as cultural practice but as a valid legal source when aligned with Qur’an, Sunnah, and maqashid al-shariah. Employing empirical legal methodology, including field interviews with customary leaders and analysis of East Kalimantan Regional Regulation No. 1/2015, findings reveal that adat enriches Islamic jurisprudence by contextualizing its application, ensuring social harmony, and preserving cultural identity. This study affirms that adat, when fulfilling juristic conditions, is not merely tolerated but actively integrated into Islamic legal frameworks proving Islam’s adaptability as a living, contextual, and universal legal system. Keywords: custom, fiqh maxim, , Islamic law, legal determination, maqashid shariah, Kenyah adat, socio-legal integration